Non-Christian currents in modern Ukraine - Tytarenko, Vita Volodymyrivna (Ukrai͏̈ns'ke relihijeznavstvo, 2008)
Non-traditional religious entities are no longer a marvel on the territory of Ukraine. Some are on the margins, and some, including non-Christians, are quite active and talkative. Non-Christianity in religious literature means those religious trends that occur within traditional Christianity, modernizing it in the context of secularization of social consciousness, scientific and technological and information revolution, social and ecological cataclysms, and offering to man a spiritual and fundamental basis, which is a spiritual and spiritual basis, a world of answers to constant existential inquiries.